Produktivitas Komunitas Belajar Dalam Meningkatkan Pengelolaan Pembelajaran Guru Sekolah Dasar - Angela Sari, Trisa; nur sasongko, rambat (Manajer Pendididikan, 2025)
This study aims to describe the productivity of learning communities in improving learning management at SDN Taba Renah, Musi Rawas Regency, focusing on lesson planning, implementation, and evaluation. This research employs a qualitative descriptive method, utilizing interviews, observations, and documentation for data collection. The findings indicate that learning communities play a significant role in developing teaching modules, integrating technology, and facilitating reflective teaching practices. Supporting factors include school leadership support and teacher collaboration, while challenges involve disparities in technological proficiency and limited time for peer observation. Overall, the learning community at SDN Taba Renah has made a positive contribution to learning management and supports the implementation of the Merdeka Curriculum.